Pengukuran Performa Pengiriman Data Absensi Menggunakan Simple Object Access Protocol dan ZKEM Control Pada Mesin Fingerprint - Sopian Alviana (Komputika : Jurnal Sistem Komputer, 2020)
The use of fingerprint machine as access attendance data has been widely used, both by the organization and the company. In the application, each attendance data is stored on the fingerprint machine, then the data can be withdrawn with various systems and processed further. Sometimes, some application developers use existing applications for the process of retrieving attendance data manually or with existing applications then done data processing with the application that has been created. Manual processing is usually done by retrieving data using storage media such as flashdisks and then exporting the data to the database. In addition, you can use the method by utilizing the facilities provided by simple Object Access Protocol and ZKEM control. In the research comparing the performance of both facilities in sending attendance data from the fingerprint machine to the database. The performance measured is the speed of data transmission and the accuracy of the amount of data transmitted by the fingerprint machine. The results obtained in this research that the delivery of attendance data using Simple Object Access Protocol and ZKEM control have the same data accuracy. Meanwhile, in terms of time delivery ZKEM control can send data 50% faster than using Simple Object Access protocol.